Daya Tarik Pemasaran, Digital Shopee Dengan Menggali Pengaruhnya Terhadap Loyalitas Pelanggan Milenial dan Gen Z - Octaviani , Rini; Budi Harto; Andina Dwijayanti; Lina Parlina; Panji Pramuditha; Sulistianingsih (Program Studi Administrasi Bisnis, 2025)
The purpose of this study is to understand the impact of Shopee's digital marketing strategies on customer loyalty among Generation Z and Millennials. Shopee, one of the largest e-commerce platforms in Southeast Asia, uses various digital marketing strategies, such as personalization, social media, loyalty programs, and interactive campaigns. This study uses a quantitative approach to analyze survey data collected from more than 100 respondents who are active Shopee users in the Millennial and Gen Z communities. The research findings show that Shopee's digital marketing features, such as creative content, personalized promotions, and ease of transactions, have a noteworthy positive impact on customer loyalty. These factors influence users' level of trust, loyalty, and desire to continue using the platform. This study highlights the importance of innovation in digital marketing strategies to increase customer loyalty, especially among the younger generation.